Pengaruh Experiental Marketing Terhadap Loyalitas Pelanggan Yang Dimediasi Oleh Kepuasan Pelanggan Dan Brand Trust - Risqy Aziz Basuki; Maediana Rahayuning Tyastuti (JOURNAL FOR BUSINESS AND ENTREPRENEURSHIP, 2020)
This research aims to determine the influence of experiental marketing on customer loyalty mediated by satisfaction and brand Trust at PT. PBM Bandar Krida Jasindo. The population in the study consisted of 81 companies who were PBM BKJ customers. The sampling technique in this study uses Yamane formula 5%, resulting in 68 customers that shorten the sample selection criteria. The results of the study showed Experiental marketing variables affecting customersatisfaction with the value of Original Sample = 0.841 T Statistics = 23.024 > 1.96 P Value = 0.000. The Experiental marketing variable affects the brand trust with the Original Sample value = 0918 T Statistics = 0.858 > 1.96 P Value = 0.000. Experiental Marketing variables do not necessarily affect customer loyalty with the Original Sample value =-0.055 T Statistics = 0.331 < 1.96 P Value = 0741. Customer Satisfaction variables affect customer loyalty with value Original Sample = 0.352 T Statistics = 3.407 > 1.96 P Value = 0000. The brand trust variable affects customer loyalty with the Original Sample value = 0.620 T Statistics = 5.038 > 1.96 P Value = 0.000. Mediation of customer satisfaction is able to increase the influence of experiental marketing towards customer loyalty with Original Sample value = 0.532 T Statistics = 5.041 > 1.96 P Value = 0.000. The mediation of brand trusts is able to add a marketing experiental effect to customer loyalty with the value of Original Sample = 0.297 T Statistics = 3.338 > 1.96 P Value = 0.001. Gained experiental marketing results have a positive and significant effect on customer satisfaction, Experiental marketing has positive and significant effect on brand trust, Experiental Marketing has positive and significant effect on customer loyalty, customer satisfaction has positive and significant effect on customer loyalty, brand Trust has positive and significant effect on customer loyalty, customer satisfaction mediation have positive and significant effect on customer loyalty, mediation of brand trusts is capable of adding experiental marketing influence to customer loyalty. Keywords: experiental marketing, customer loyalty, customer satisfaction, brand trust